Catalytic activation of nitriles towards nucleophilic addition - Lester, Roy P. (2015)
The work presented in this thesis is focused on the development of a multifaceted approach to the catalytic activation of nitriles. To develop a versatile method for catalytic nitrile activation two probes were utilised; i) the development of a direct synthesis of allylic amides from the corresponding allylic alcohol and nitrile using a commercial platinum salt, together with a detailed mechanistic investigation into the process, ii) the direct synthesis of 2-bezoxazole from the corresponding 2-aminophenol and nitrile with the aid of a commercial platinum salt as well as the use of alcoholic solvents. In addition to nitrile activation a preliminary study on the application and further functionisation of 2-trichlorobenzoxazoles was undertaken. i) A novel multifaceted approach to the direct synthesis of allylic amides via the catalytic activation of di- and trichloroacetonitrile will be discussed. This one-pot methodology relies on the same platinum catalyst to activate a nitrile towards nucleophilic attack of allylic alcohol as well as activate the newly formed allylic imidate towards a [3,3]-sigmatropic rearrangement, which produced a number of allylic amides. In addition to the development of the one-pot allylic amide methodology a number of mechanistic studies including 1H, 13C{1H} and gas chromatography were under taken to better understand the process.